Analisis ekspor minyak nabati Indonesia dan faktor-faktor yang mempengaruhinya - Apriade, Muhammad; Tan, Syamsurijal; Nurjanah, Rahma (e-Journal Perdagangan Industri dan Moneter, 2018)
This study aims to analyze the development of the value, rate, inflation of international prices and Indonesian vegetable oil exports and the effect of weight, inflation, and global prices on Indonesian vegetable oil exports. The data analysis method used is descriptive and quantitative methods. The data analysis tool used is the OLS (Ordinary Least Square) method. Include data for the years 2000-2018. The data analysis technique is multiple linear regression, hypothesis testing using F-test, and simultaneously using t-test. Based on the simultaneous research results, inflation and international prices significantly affect Indonesia's vegetable oil exports. Keywords: Vegetable oil export value, Exchange rate, Inflation, Global prices